2012
DOI: 10.1371/journal.pone.0035992
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Inflammation Responds to Microbial Tissue Load Independent of Pathogen/Non-Pathogen Discrimination

Abstract: The intestinal immune system mounts inflammatory responses to pathogens but tolerates harmless commensal microbiota. Various mechanisms for pathogen/non-pathogen discrimination have been proposed but their general relevance for inflammation control is unclear. Here, we compared intestinal responses to pathogenic Salmonella and non-pathogenic E. coli. Both microbes entered intestinal Peyer’s patches and, surprisingly, induced qualitatively and quantitatively similar initial inflammatory responses revealing a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Thus, genes controlling these first few hours of response to pathogen invasion are likely gene candidates for resistance traits. However, if this does not result in elimination or destruction of the micro-organism, then the tissue load (Willer et al, 2012), and whether the micro-organism is alive or dead (Fontana and Vance, 2011), in other words sensing micro-organism growth in tissues, may become more important determinants of immunopathology. In this second phase, the host may detect micro-organism derived metabolic molecules such as mRNA or bacterial pyrophosphates.…”
Section: Identity Of Candidate Resistance and Tolerance Genesmentioning
confidence: 99%
“…Thus, genes controlling these first few hours of response to pathogen invasion are likely gene candidates for resistance traits. However, if this does not result in elimination or destruction of the micro-organism, then the tissue load (Willer et al, 2012), and whether the micro-organism is alive or dead (Fontana and Vance, 2011), in other words sensing micro-organism growth in tissues, may become more important determinants of immunopathology. In this second phase, the host may detect micro-organism derived metabolic molecules such as mRNA or bacterial pyrophosphates.…”
Section: Identity Of Candidate Resistance and Tolerance Genesmentioning
confidence: 99%
“…Kim et al [ 5 ] and Huang et al [ 20 ] found that P. linteus organic extracts inhibited NF-κB, MMP-9 and MAPK activation in vivo and in vitro , leading to the conclusion that P. linteus may present a therapeutic approach for inflammation-associated disorders such as rheumatoid arthritis, psoriasis and other autoimmune afflictions. Shnyreva et al [ 21 ] found that treatment of K562 cells with P. linteus ethanol extract increased the expression of the anti-inflammatory cytokine IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…Johansson et al ., ), making it unlikely that the E. cyathigerum genotypes present at a given waterbody would never have encountered E. coli in other waterbodies. Furthermore, an immune response to familiar non‐pathogenic bacteria has been observed before and interpreted as immune priming of the host (Freitak et al ., , ) or the inability to distinguish between pathogenic and non‐pathogenic bacterial challenges (Willer et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with non‐pathogenic bacteria have been ignored in the context of trade‐offs underlying the maintenance of variation in immune function (Sheldon & Verhulst, ; Schmid‐Hempel, ). Yet, it has recently been documented that exposure to non‐pathogenic bacteria can activate the immune system (Freitak et al ., ; Freitak, Heckel & Vogel, ; Willer, Müller & Bumann, ). We therefore hypothesise that non‐pathogenic bacteria may also increase vulnerability to predation, hence may play a role in the maintenance of variation in immune defence.…”
Section: Introductionmentioning
confidence: 99%